2009
DOI: 10.1016/j.ejcts.2009.01.024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fenoldopam and dopexamine on hepatic blood flow and hepatic function following coronary artery bypass grafting with hypothermic cardiopulmonary bypass

Abstract: Fenoldopam infusion induced transient tachycardia, with no augmentation of hepatic blood flow whereas dopexamine induced tachycardia and did not augment hepatic blood flow. Fenoldopam and dopexamine may have hepato-protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…the three determinants of lBF are intestinal vascular resistances that determine the intestinal flow and portal vein flow, the arteriolar resistances in the territory of the hepatic artery and the intrahepatic resistances to portal flow that are less important than mesenteric resistances 24 . Furthermore, there is a buffer mechanism in the hepatic arterial circulation that forms a feedback between the portal flow and vascular resistances in the hepatic artery so that when PVQ increases the resistance of the hepatic artery also increases 21,[24][25][26][27] . On the other side, the arterial liver circulation lacks self-regulation which means that the relationship between perfusion pressure of the liver and lBF flow is linear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the three determinants of lBF are intestinal vascular resistances that determine the intestinal flow and portal vein flow, the arteriolar resistances in the territory of the hepatic artery and the intrahepatic resistances to portal flow that are less important than mesenteric resistances 24 . Furthermore, there is a buffer mechanism in the hepatic arterial circulation that forms a feedback between the portal flow and vascular resistances in the hepatic artery so that when PVQ increases the resistance of the hepatic artery also increases 21,[24][25][26][27] . On the other side, the arterial liver circulation lacks self-regulation which means that the relationship between perfusion pressure of the liver and lBF flow is linear.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also other mechanisms that can affect liver flow in patients undergoing major general and cardiac surgery 1,4,5 including the effect of halogenated anaesthetics 8 , assisted ventilation 1,28 and short-term haemodynamic fluctuations that reduce lBF. the effect of other drugs on lBF with a potent systemic vasodilator capacity is variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…# = PDR -Percentage disappearance rate t 1/2 -Half life for clearance of the dye measured in minutes Calculating the PDR rather than the clearance itself eliminates the need to ensure that an accurate dose of ICG was given, since clearance is calculated from the product of elimination rate constant (log e 2/t 1/2 ) and the volume of distribution (dose of dye/concentration at time zero) 6 .…”
Section: Protocolmentioning
confidence: 99%
“…Cardiac output during CPB remains completely dependant on the pump flow, particularly following application of the crossclamp. In an earlier study, we have demonstrated that pharmacological agents like dopexamine and fenoldopam (another DA-1 receptor agonist) do not increase hepatic blood flow 6 . Limited studies have examined the effects of higher pump flow on cerebral blood flow 7 , renal function in humans 8 and splanchnic perfusion in rabbits 9,10 .…”
Section: Introductionmentioning
confidence: 97%